Iowa Birdline update, September 5-6, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for September 5-6, 1994. The highlight of the update was the discovery of a Long-tailed Jaeger at Tomahawk Marsh. Also of note was the first fall report of a Red-breasted Nuthatch as well as observations of numerous Warbler species, including Mourning and Golden-winged. Also included are handwritten notes for the next week's update with sightings of a Hooded Warbler, a White-eyed Vireo, and a Le Conte's Sparrow. Epson - sheet feed/flatbed